The world economy still at risk - Günter Großer; Günter Weinert (Intereconomics, 1993)
Following the prolonged upswing in the world economy during the eighties, the subsequent downturn is proving to be more persistent than expected. It looks as if the USA is now at last on the road to recovery but Japan and Western Europe are still having a tangible dampening effect at the turn of the year. Are there prospects for an improvement in the world economy for 1993?
Keywords: 330; Economic Trends